การศึกษาสภาพการใช้หลักสูตรท้องถิ่นของโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาเขต 5 จังหวัดลพบุรี - อินไชย, สุรีย์พร; สุดรุ่ง, จุไรรัตน์ (An Online Journal of Education, 2018)
The objectives of this research were to study of implementing a local curriculum of the secondary schools in the secondary educational service area office 5, Lopburi. The population studied in the research were administrators, vice principals or chiefs academic and teachers. At Lopburi schools altogether 100 persons. The instrument used in this research was a set of questionnaire. Statistics methods used in data analysis were frequency, percentage, average and standard deviation. Research findings were as follow; Considering each side in Curriculum management found that the highest was Curriculum analysis. The average is 4.04 in high level. The second was in medium level is The provision of various facilities to the curriculum. The average is 3.96 in medium level and Recruitment teachers is in the medium level. The average is 3.94. Teaching tasks found that the highest was Measurement and evaluation of learning. The average is 3.94 and in medium level. The second was Learning and Activities management. The average is 3.76 in the medium level. And Remedial teaching is in the medium level. The average is 3.71